Functional role of UNC13D in immune diseases and its therapeutic applications - Duong, Van-Thanh; Lee, Dongjun; Kim, Yun Hak; Oh, Sae-Ock (Frontiers in Immunology, 2024)
UNC13 family (also known as Munc13) proteins are evolutionarily conserved proteins involved in the rapid and regulated secretion of vesicles, including synaptic vesicles and cytotoxic granules.Fast and regulated secretion at the neuronal and immunological synapses requires multiple steps, from the biogenesis of vesicles to membrane fusion, and a complex array of proteins for each step.Defects at these steps can lead to various genetic disorders. Recent studies have shown multiple roles of UNC13D in the secretion of cytotoxic granules by immune cells. Here, the molecular structure and detailed roles of UNC13D in the biogenesis, tethering, and priming of cytotoxic vesicles and in endoplasmic reticulum are summarized. Moreover, its association with immune diseases, including familial hemophagocytic lymphohistiocytosis type 3, macrophage activation syndrome, juvenile idiopathic arthritis, and autoimmune lymphoproliferative syndrome, is reviewed. Finally, the therapeutic application of CRISPR/Cas9-based gene therapy for genetic diseases is introduced.